Interferon + bevacizumab – a new generation of renal cell cancer immunotherapy? - Wysocki, Piotr J. (Contemporary Oncology/Współczesna Onkologia, 2009)
For many years renal cell cancer (RCC) has been supposed to be resistant to systemic treatment. The growth and progression of RCC, which is known to be an immunogenic tumour, is tightly controlled by the immune system. In order to escape from immune surveillance, RCC downregulates surface molecules and tumour-associated antigens, as well as induces local and systemic immunosuppression by secreting VEGF, TGF-b, IL-4 and IL-10. Through the 1990s immunotherapy based on INF-a and IL-2 was the treatment of choice in metastatic RCC (mRCC). However, the efficacy of cytokine-based immunotherapy was moderate and was associated with significant toxicity. During the last 5 years the introduction of novel targeted therapies has made tremendous progress in the treatment of mRCC. Since these targeted agents (bevacizumab, sorafenib, sunitinib, temsirolimus, everolimus) act mainly on tumour vasculature, their activity seems to be cytostatic rather than cytotoxic. Consequently, the targeted agents cannot cure mRCC patients, but can induce long-lasting disease stabilization. On the other hand, immunotherapy remains the only strategy that may potentially cure mRCC patients. Neutralization of serum VEGF not only demonstrates a strong anti-angiogenic effect, but may also inhibit the VEGF-induced immunosuppression. Combination of immunotherapy (IFN-a) with neutralization of VEGF (bevacizumab) seems to represent a novel immunotherapeutic approach. It is possible that this strategy may induce long-lasting complete clinical responses and even cure some good-risk mRCC patients